Can thyroid stimulating hormone levels by TSH (IRMA) predict relapse of thyrotoxicosis following carbimazole treatment? - Wilson, R. (BMJ Group, 1987)
Serum thyrotrophin receptor antibody (TRAb) and thyroid stimulating hormone (TSH) (IRMA) levels were measured in 38 patients at one month after the end of a course of carbimazole/T3 therapy for Graves' disease. Despite the increased sensitivity of the IRMA assay a TSH measurement at this stage was found to be of no predictive value, in contrast to estimation of serum TRAb levels which correctly predicted relapse and remission in 90% of patients.